Use of heart rate to predict energy expenditure of sheep on range land - Shinde, A K; Karim, S A; Singh, V P; Sankhyan, S K (The Indian Journal of Animal Sciences, 2012)
Heart rate and energy expenditure of adult Malpura sheep were recorded in the morning (0600 hr) and night (2200 hr) while at rest in animal shed and during grazing on pasture at peak hot period (1400 hr) in different seasons. Correlation of heart rate with energy expenditure showed a positive linear relationship (r=0.54) in different hours of recording and distinct differences were noticed between resting and grazing condition. Regression equation developed from heart rate (beat/min) and energy expenditure (Kcal/hr) of sheep while grazing on pasture was EE=2.86+0.88b (r=0.47; n=30). It is concluded that the developed equation could predict the BE of range managed sheep from heart rate with 77 % confidence.